Outcomes of children born to mothers with systemic lupus erythematosus exposed to hydroxychloroquine or azathioprine. (29th June 2022) - Reynolds, John A; Gayed, Mary; Khamashta, Munther A; Leone, Francesca; Toescu, Veronica; Bruce, Ian N; Giles, Ian; Teh, Lee-Suan; McHugh, Neil; Akil, Mohammed; Edwards, Christopher J; Gordon, Caroline
Abstract: Objectives: HCQ and AZA are used to control disease activity and reduce risk of flare during pregnancy in patients with SLE. The aim of this study was to determine the outcomes of children born to mothers with SLE exposed to HCQ or AZA during pregnancy and breast-feeding. Methods: Women attending UK specialist lupus clinics with children ≤17 years old, born after SLE diagnosis, were recruited to this retrospective study. Data were collected using questionnaires and from clinical record review. Factors associated with the outcomes of low birth weight and childhood infection were determined using multivariable mixed-effects logistic regression models. Results: We analysed 284 live births of 199 mothers from 10 UK centres. The first pregnancies of 73.9% of mothers (147/199) were captured in the study; (60.4%) (150/248) and 31.1% (87/280) children were exposed to HCQ and AZA, respectively. There were no significant differences in the frequency of congenital malformations or intrauterine growth restriction between children exposed or not to HCQ or AZA. AZA use was increased in women with a history of hypertension or renal disease. Although AZA was associated with low birth weight in univariate models, there was no significant association in multivariable models. In adjusted models, exposure to AZA was associated with increased reports of childhood infection requiring hospital management [odds ratio 2.283 (1.003, 5.198), P = 0.049]. Conclusions: There were no significant negative outcomes in children exposed to HCQ in pregnancy. AZA use was associated with increased reporting of childhood infection, which warrants further study.